Off-line ESI-MS/MS profiling of betalains and flavonoid glycosides isolated from (fruit) Opuntia stricta var. dillenii and (vegetable) Atriplex hortensis var. rubra by countercurrent chromatography - Thi Minh Thu Tran; Thanh Binh Nguyen; Peter Winterhalter; Gerold Jerz (Vietnam Journal of Science, Technology and Engineering, 2022)
Opuntia stricta var. dillenii and Atriplex hortensis var. rubra, two plant species with abundant betalain and flavonoid content, were studied by high performance countercurrent chromatography (HPCCC) coupled with ESI-MS/ MS in an off-line detection process. Both CCC runs used tert.-butyl-methyl-ether/n-butanol/acetonitrile/water 1% trifluoroacetic acid (v/v/v/v, 2:2:1:5) as a biphasic solvent system within an elution-extrusionmode. The resulting fractions were scanned by an off-line sequential injection to ESI-MS/MS approach. The separation of Opuntia stricta var. dillenii extract showed a partial isolation of principal betalains (betanin) from their derivatives (betanidin, phyllocactin, feruloyl-betanin, betaxanthin), degraded products (hydroxyl-neobetanin, mono decarboxy-betanins), and flavonoid glycosides (isorhamnetin-rutinoside, kaempferol-rutinoside). In case of Atriplex hortensis var. rubra, this study confirmed the coexistence of several flavonoids (quercetin-Omalonyl glucoside, kaempferol-O-malonyl glucoside) and generated few pure pigment fractions (celosianin II) for structural elucidation. These findings are consistent with earlier research on the use of CCC for the separation of flavonoids and betalain from these two plants. This work also shows that the CCC all-liquid separation technology may be used to recover bioactive chemicals on a larger scale from plant materials of Atriplex hortensis and Opuntia stricta.